Peran Pustakawan di Era Digital (Studi Kasus Perpustakaan Dikti Idrisiyyah) - Zulfani Jannah Hamidah; Ulfi Wisa Belinda; Emy Sri Wahyuni (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aims to analyze the vital role of librarians in the digital era, particularly at the Idrisiyyah Dikti Library. The applied method is descriptive and collects data through various techniques, including literature studies, observations, and interviews. The results of the study indicate that librarians play a crucial role in educating users to effectively utilize digital technology. Additionally, librarians contribute to the innovation of library services, although they still face challenges in the public's understanding of digital collections. Recommendations from this research include the need for sustainable policy support to enhance librarians' capacity and strengthen the evaluation system in the implementation of library services, thereby achieving better educational outcomes.